(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Tuberculosis remains one of the most significant infectious diseases worldwide, posing substantial challenges to public health due to its high prevalence and mortality. Early and accurate diagnosis is essential for effective disease control and successful treatment outcomes. This review examines the current laboratory and instrumental methods used in the diagnosis of tuberculosis, including microbiological, molecular, immunological, and imaging techniques. The diagnostic capabilities, advantages, and limitations of these approaches are discussed. The combined application of laboratory and instrumental investigations improves the detection of both active and latent tuberculosis, facilitates timely therapeutic interventions, and enhances patient monitoring. The integration of modern diagnostic technologies plays a crucial role in improving clinical outcomes and reducing the global burden of tuberculosis.